Cod and nitrogen removal of aerobic granular sludge in seafood processing wastewater treatment. - Nguyen, Phuoc-Dan (Asean Engineering Journal)
Aerobic granule was formed and stably in the sequencing batch airlift reactor with the seafood processing wastewater at different organic loading rates (OLR) and nitrogen loading rates (NLR). At the N/COD ratio of 0.1, the COD removal efficiency was ranging from 94 to 96 percent for OLR of 2.6-7.2 kg COD/m3d. The TKN removal efficiency was 93, 94 and 79 percent, respectively. A the varied N/COD ratios, the TKN removal efficiency was approximately 95 percent for the NLR of 0.3 and 0.6 kg N/m3. d (N/COD of 0.1-0.2). The TKN removal efficiency reduced to 66 percent at the NLR of 0.9 kg N/m3 .d. In general, nitrification process occured completely at the OLR less than 4.8 kg COD/m3 .d and the NLR less than 0.6 kg N/m3 .d. The simultaneous organic and nitrogen removal was effective at the OLR of 2.6-4.8 kg COD/m3 .d and the NLRs of 0.3-0.6 kg N/m3 .d.